Root phenotypes as modulators of microbial microhabitats - Birt, Henry W. G.; Tharp, Courtney L.; Custer, Gordon F.; Dini-Andreote, Francisco (Frontiers in Plant Science, 2022)
Plant roots are colonized by a multitude of microbial taxa that dynamically influence plant health. Plant-microbe interactions at the root-soil interface occur at the micro-scale and are affected by variation in root phenotypes. Different root phenotypes can have distinct impacts on physical and chemical gradients at the root-soil interface, leading to heterogeneous microhabitats for microbial colonization. Microbes that influence plant physiology will establish across these heterogeneous microhabitats, and, therefore, exploiting variation in root phenotypes can allow for targeted manipulation of plant-associated microbes. In this mini-review, we discuss how changes in root anatomy and architecture can influence resource availability and the spatial configuration of microbial microhabitats. We then propose research priorities that integrate root phenotypes and microbial microhabitats for advancing the manipulation of root-associated microbiomes. We foresee the yet-unexplored potential to harness diverse root phenotypes as a new level of precision in microbiome management in plant-root systems.